A dinâmica da inflaç\~ao no Brasil - Alexis Maka; Fernando de Holanda Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper tests Phillips curves using an autoregressive distributed lag (ADL) specification that encompasses the New Keynesian Phillips curve (NKPC), the Hybrid Phillips curve (HPC), the Sticky-Information Phillips curve (SIPC), and the accelerationist Phillips curve (APC). We use data from Brazil (1996Q1-2012Q2), using the output gap and alternatively the real marginal cost as measure of inflationary pressure. The empirical evidence rejects the restrictions implied by the NKPC, the HPC, and SIPC, but does not reject those implied by the APC.
Keywords: E31; C52; 330; inflation; Phillips curve; encompassing specification